Performance investigation of a jet loop membrane bioreactor for the treatment of an actual olive mill wastewater - Değermenci, Nejdet; Cengiz, İbrahim; Yildiz, Ergun; Nuhoglu, Alper (Elsevier BV, 2016)
In this study, following the pre-treatment of olive mill wastewater (OMW), its treatment in a jet loop membrane bioreactor (JLMBR) was investigated. Among the pre-treatment options, the configuration composed of physical settling, cartridge filter and ceramic membrane showed the best performance in terms of investigated parameters. For the JLMBR that was fed by pretreated OMW, up to 93 and 87% removal efficiencies were achieved for the chemical oxygen demand (COD) and total phenol, respectively, at volumetric organic load (VOL) of 17.8 kg COD/m3 day. The calculated specific oxygen uptake rate (SOUR) values were in the range 7.7-34.7 g O2/kg MLVSS h. When even hydraulic retention times (HRT) values decreased by a factor of 1:24, system performance in terms of COD and total phenol removal remained almost stable. Decreasing the sludge retention time (SRT) to three days made considerable perturbations for the system performance, increasing the effluent COD and total phenol values in 900 and 80 mg/L, respectively. The JLMBR showed a high overall performance for the treatment of an actual OMW under the evaluated operational conditions.
Keywords: jet loop membrane bioreactor; food industry; Wastewater; Waste Disposal, Fluid; bioreactor; Bioreactors; equipment design; Jet loop reactor; phenol; pollutant removal; Olive mill wastewater; anoxic conditions; Sewage; pH; Equipment Design; oxygen consumption; wastewater treatment; retention time; Membrane bioreactor; devices; conductance; Industrial Waste; waste water management; chemistry; olive tree; Article; industrial waste; Aerobic treatment; chemical oxygen demand; bioremediation; Olea; sewage; Waste Water; procedures; Food-Processing Industry; Biological Oxygen Demand Analysis; olive mill wastewater; waste water; Phenol; isolation and purification; membrane reactor; sludge; jet flow; biochemical oxygen demand; performance assessment; effluent; 6. Clean water; 3. Good health